2014
DOI: 10.1002/2014wr015581
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain ecohydrology: Climatic, anthropogenic, and local physical controls on partitioning of water sources to riparian trees

Abstract: Seasonal and annual partitioning of water within river floodplains has important implications for ecohydrologic links between the water cycle and tree growth. Climatic and hydrologic shifts alter water distribution between floodplain storage reservoirs (e.g., vadose, phreatic), affecting water availability to tree roots. Water partitioning is also dependent on the physical conditions that control tree rooting depth (e.g., gravel layers that impede root growth), the sources of contributing water, the rate of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 77 publications
1
69
0
Order By: Relevance
“…Isotope tree-ring studies can provide detailed, historical records of the ecohydrological processes occurring during the time of growth, including the source-water uptake, for riparian forests (Alstad et al, 2008;Marshall and Monserud, 2006;Singer et al, 2013;Singer et al, 2014). This is achieved through analysis of oxygen isotope ratios within tree-ring cellulose (δ 18 O cell ), which preserves a signal from source water used by trees during growth.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isotope tree-ring studies can provide detailed, historical records of the ecohydrological processes occurring during the time of growth, including the source-water uptake, for riparian forests (Alstad et al, 2008;Marshall and Monserud, 2006;Singer et al, 2013;Singer et al, 2014). This is achieved through analysis of oxygen isotope ratios within tree-ring cellulose (δ 18 O cell ), which preserves a signal from source water used by trees during growth.…”
Section: Introductionmentioning
confidence: 99%
“…Barbour et al, 2004;Roden et al, 2000) have demonstrated successes in predicting cellulose δ 18 O cell from a known source-water signature (δ 18 O sw ) by accounting for the relevant environmental and physiological parameters driving the fractionation of oxygen isotopes before the incorporation into cellulose. By accurately constraining these variables it is possible to use δ 18 O cell to determine the δ 18 O sw used during the growing season (Singer et al, 2014). Yet, such annual (whole-ring) analyses only provide an integrated signal of water-use over the entire growing season (Alstad et al, 2008;Marshall and Monserud, 2006;Singer et al, 2013;Singer et al, 2014), which may belie seasonal dynamics in water availability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2006c) for a steeply rising 20 topography in the Daly River, this is unlikely to be attributable to increased elevation since the change in elevation was minimal across each entire transect (< 3 m), and even smaller near Allungra Creek where most of the change in Δ 13 C was recorded. Therefore the cause of the change in Δ 13 C with distance from the creek was most likely to be a function of the frequency with which trees receive flood water and hence the amount of recharge into the soil profile (Ehleringer and Cooper, 1988;Thorburn et al, 1994;Villeneuve et al, 2015;Singer et al, 2014). We therefore further conclude that foliar 25 Δ 13 C can be used as an indicator of access to additional water to that of rainfall, regardless of the source of that additional water (e.g., groundwater, flood recharged soil water storage, irrigation).…”
Section: Patterns Of Carbon Isotope Discrimination and Intrinsic Watementioning
confidence: 99%